Services of General Interest Beyond the Single Market
XII, 401 p. 8 illus., 7 illus. in color.
Keywords: This is the first book ever to assess comprehensively the impact of EU international agreements on services of general interest. Services of general interest remain high on the political and legal agenda of the European Union. However, the debates about the impact of EU law on services of general interest usually focus on internal market law such as the free movement of services, competition law, state aid rules and the law of public procurement. The external and international dimensions of the European legal framework for services of general interest are often overlooked. This book addresses the impact of international trade and investment agreements on public services and the role these services play in EU external relations. It shows that the inherent tension between establishing and securing undistorted competition on markets and the logic of public services exists in international economic law in a similar way as in EU internal law. Given the contentiousness of international trade and investment agreements as well as the EU’s external policies, the issues discussed in this volume are timely and relevant and contribute to the ongoing debate about the future of services of general interest in the EU with fresh ideas and perspectives. Markus Krajewski is Professor of Public and International Law at the University of Erlangen-Nuremberg, Germany.